Antennal Morphology and Sexual Dimorphism of Antennal Sensilla in Callitettix versicolor (Fabricius) (Hemiptera: Cercopidae) - Qing Zhu; Nan Wu; Jolanta Brożek; Wu Dai (Insects, 2019)
The rice spittlebug Callitettix versicolor (Fabricius) is an important pest of rice and maize in South Asia and causes severe economic damage. To provide background information for chemical ecology studies, the fine morphology of antennae and the types and distribution of the sensilla on the male and female antennae of Callitettix versicolor (Fabricius) are investigated by means of scanning electron microscopy (SEM). Results show that the antenna is filiform and composed of three segments: a scape, a pedicel, and a flagellum. The female antennae are slightly shorter than the male antennae. In both sexes, four types and nine subtypes of sensilla were observed: sensilla basiconica (SB1, SB2), sensilla campaniformia (SCa1, SCa2 and SCa3), sensilla coeloconica (SCo1, SCo2 and SCo3) and sensilla trichodea (ST). In addition, sensilla coeloconica (SCo1) are observed on the membrane of the top of the pedicel in Cercopidae for the first time. Sexual dimorphism mainly occurs in variation in the number of sensilla coeloconica (SCo2, SCo3) on the bulb-shaped portion of the flagellum and in the shape of sensilla basiconica (SB2). There are significantly more sensilla coeloconica in males than in females. The external structure and distribution of these sensilla are compared to those of other cercopids and possible functions of the antennal sensilla are discussed.